Keamanan Jaringan dengan Metode Access List Demilitarized Zone (DMZ) pada Cisco RV042 - Taufik Rahman; Rifqy Muzhaky Adha (Jurnal Inovtek Polbeng Seri Informatika, 2021)
Increasing users of mobile-based applications, making the network the backbone for every organization. It is very important to secure the network. Because many heterogeneous devices such as desktops, laptops, tablet pc, smartphones are connected on the network. Security is an important issue in the design and deployment of enterprise networks. Protecting servers from various network attacks and becomes a challenging task in providing security to servers and networks. Some of the challenges are, attacks that come from local networks other than the internet, connecting servers with internet and intranet networks. PT. Sarana Sistem Mikro is a company that relies heavily on fast and secure information access. So it takes the development of existing computer networks at PT. Micro System Facilities. In conducting the analysis, using data collection methods, interviews, literature studies and research methods by conducting needs analysis, design, testing and implementation. Designing a network using the De-Militarized Zone method so that the network runs safely and optimally. And the results applied to the DMZ method, a network security system at PT. Micro System Facilities are maintained